Cleaner Energy Storage: Cradle-to-Gate Life Cycle Assessment of Aluminum-Ion Batteries With an Aqueous Electrolyte - Melzack, N; Wills, RGA; Cruden, A (Frontiers in Energy Research, 2021)
In the context of growing demand on energy storage, exploring the holistic sustainability of technologies is key to future-proofing our development. In this article, a cradle-to-gate life cycle assessment of aqueous electrolyte aluminum-ion (Al-ion) batteries has been performed. Due to their reported characteristics of high power (circa 300 W kg−1 active material) and low energy density (circa 15 Wh kg−1 active material), these results were compared with those of supercapacitors (per kW). Initial findings suggest these aluminum-ion cells have fewer environmental impacts than commercial supercapacitors, hence offering a more environmentally sensitive energy storage technology solution. Al-ion batteries are in their early development, and this result shows a strong argument for continuing research into this technology alongside other emerging energy storage systems.